2022
DOI: 10.1021/acs.jpcc.2c06508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Next-Nearest-Neighbor Aluminum Location on the Brønsted Acidity of HY Zeolites

Abstract: The distribution of aluminum (Al) on the H-form zeolite framework strongly affects the Brønsted acidity, resulting in the corresponding acid-catalyzed reactivity of zeolite catalysts. In the present work, the effects of next-nearest-neighbor (NNN) Al locations and numbers on the acidity for the specific Brønsted acid sites (BAS) inside the channel and on the external surface of the HY zeolites with two Si/Al ratios were investigated using density functional theory calculations. The Gibbs free energy of ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For low Si/Al ratios, a repulsion between ammonia ions can further decrease the adsorption heats. In contrast, it has been shown that the interaction with the nearest neighbor Al atoms can play an important role, and thus a comparison/interpretation of theoretical and experimental values is difficult unless proton distributions along with ammonia loading are treated in the correct statistical fashion for medium to lower Si/Al ratios 15 , 24 , 59 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For low Si/Al ratios, a repulsion between ammonia ions can further decrease the adsorption heats. In contrast, it has been shown that the interaction with the nearest neighbor Al atoms can play an important role, and thus a comparison/interpretation of theoretical and experimental values is difficult unless proton distributions along with ammonia loading are treated in the correct statistical fashion for medium to lower Si/Al ratios 15 , 24 , 59 .…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of probe base molecules in zeolites is one of the most used techniques to access aluminosilicate's acidity and properties (Fig. 1B) [20][21][22][23][24][25][26][27][28][29][30] . Hydrogen-bonded complexes or ionic pairs are formed in dependence on the proton affinity (PA) of the base probe and temperature.…”
Section: Investigation Of Brønsted Acidity In Zeolites Through Adsorb...mentioning
confidence: 99%
“…Density functional theory (DFT) calculations are widely acknowledged as a valuable tool for gaining insight into the structure–performance relationship of zeolite-supported metal catalysts at the atomic level . In a study by Garnica et al the isomerization reaction of 1,2-dihydrophenanthrene catalyzed by mordenite zeolite was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) calculations are widely acknowledged as a valuable tool for gaining insight into the structure−performance relationship of zeolite-supported metal catalysts at the atomic level. 15 In a study by Garnica et al 16 the isomerization reaction of 1,2-dihydrophenanthrene catalyzed by mordenite zeolite was investigated. They found that the electrostatic adducts, resembling ion-pairs and π complexes commonly observed in zeolite catalysts, play a crucial role in enabling the reaction to proceed through an energetically favorable pathway and account for its selectivity.…”
Section: Introductionmentioning
confidence: 99%